Ectopia Cordis Sternalis with Cantrell Syndrome in a Goat Kid (Capra hircus) – A Case Report - Nair, Sudheesh S.; Jennes, Deny; Hansoge, Anvitha; Ramankutty, Soumya; Anoop, Sainulabdeen; John Martin, K. D. (International Journal of Livestock Research, 2021)
Ectopia cordis is a congenital condition characterised by complete or partial protrusion of heart through ventral-thoraco abdominal wall defects. Ectopia cordis is usually associated with other multiple anomalies and intra-cardiac defects. This when accompanied by protrusion of other visceral organs and diaphragmatic defects are described as pentalogy of Cantrell. This short communication documents a case report of ectopia cordis sternalis with Cantrell syndrome in a day-old female goat kid presented to University Veterinary Hospital, Mannuthy. The animal had a sternal defect with a sternal cleft which exposed the heart outside the thoracic cavity lacking a functional pericardium. There was also an improper closure of umbilical opening and suspected congenital diaphragmatic hernia. The animal was presented with severe tachypnoea and apnoea and collapsed despite attempts to stabilise.